Voting Patterns in Western European Countries. Class-Party Family Alignments and Their Mediation by Political Values - Marchesi, Andrea (Frontiers in Political Science, 2022)
This article investigates voters’ preferences for party families in Western European countries’ gen-eral elections in the 2000s. According to the realignment literature, ‘traditional’ class voting pat-terns have been replaced by new class-party alignments: upper-middle employee classes joined the electoral bases of left parties, whereas radical right actors introduced in the electoral competition of the most deprived strata of the population, labelled ‘left behind’. This article aims to answer to the research questions: do social class and political values affect voting behaviour in Western European general elections? Which direction are these variable associated to the preference of party families? The first section outlines the theoretical framework, accounting for the ‘societal modernization’ processes which have been affecting Western societies since the late 1960s. Among the ‘traditional’ cleavages, the literature assumes the realignment of class voting patterns, as well as alignments be-tween value orientations and political preferences. Indeed, class-party alignments are mediated by the political supply’s mobilization of voters according to their value orientations. Such appeals dif-fer among party families, partly explaining why specific classes constitute their electoral bases or contested stronghold. The theoretical framework hypothesizes political values as clustered in three ideologies (social and economic conservatism-liberalism, and authoritarianism-libertarianism). Those political values which do not assimilate in ideologies constitute more proximal factors, i.e. evaluations of specific political issues close to elections (attitudes). Having defined class voting re-alignment and a theoretical account of value voting, the paper empirically investigates their associ-ations with vote choices in Western Europe. The analyses ground on European Social Survey data, aggregating the responses concerning the twelve Western European countries for which data is available in all waves. The dependent variable clusters the parties which competed in the general elections occurred in the time span considered in party families. Fixed effects multinomial logistic regression models are performed to detect which social classes constitute party families’ bases or contested stronghold and how more proximal variables, based on values, account for class voting patterns. The results clearly show whose social classes are more likely to have voted for radical left, center-left, center-right and radical right party families.